Unveiling students’ writing argumentative essays barriers in online learning - Eko Suhartoyo; Dwi Fita Heriyawati; Febti Ismiatun (Universitas Merdeka Malang, 2021)
Due to the closure of Schools and Higher Education Institutions (HEIs), HEIs had shifted the teaching and learning method from face-to-face to Screen-based learning, such as the use of Learning Management System or Moodle, and other applications. Moreover, screen-based learning, such as the use of Learning Management System or Moodle, and other applications the EFL students’ writing argumentative essays barriers in online learning as well as their learning strategies as alternative solutions to cope with them. The research employed descriptive qualitative design. The participants were six EFL students from the fifth semester who experienced writing argumentative essays during pandemic. The instrument used to gather the data was depth interviews about the issue of research. After analysis, it exposed three barriers in writing argumentative essays made by the participants, namely unusualness on the implementation of e-learning for writing, low bandwidth while learning, and students’ discouragement on writing argumentative essays. To overcome the barriers, students must be given a brief simulation previously before attending the real-time class, making classification and analogy for the complex materials up to the simple one, and get a relaxation during the argumentations class. So, it becomes a crystal clear that teacher must assist students to be aware of their weaknesses in writing argumentative essay class so that they can be more creative in writing. Besides, students are expected to be able to solve their barriers by maintaining well communication among the teachers and classmates to sharpen their understanding and implement the best learning styles individually.